Developing an In-House Biological Safety Cabinet Certification Program at the University of North Dakota. (September 2019) - Ghosh, Sumit; Voigt, Jeffrey; Wynne, Terrance; Nelson, Terrance
Introduction: Biological safety cabinets (BSCs) are the primary means of containment used in laboratories worldwide. To ensure the proper functioning of BSCs, they need to be certified annually, at a minimum, per National Sanitation Foundation (NSF)/American National Standards Institute Standard 49. Objectives: A common problem most organizations face is that in many instances, the technicians who certify the cabinets are not accredited by the NSF. Additionally, in states or regions that do not have local NSF accredited field certifiers, it takes weeks to get a service request completed, thereby delaying the research work of the laboratory. Moreover, in such instances, the cost associated with cabinet certification and repair can be very high. Materials and Methods: This led the Office of Safety at the University of North Dakota to do a thorough cost-benefit analysis of developing an in-house BSC certification program. After completing the training and testing requirements for the NSF's advanced accreditation program, the BSC certification program was initiated on campus. Results: The identified benefits led to the initiation of a program in both local and regional capacity for repair, maintenance, and certification of BSCs, and the university's experiences were shared with other universities. Conclusions: By developing an in-house BSC certification program, the University of North Dakota was able to reduce wait times associated with service repairs, reduce costs, and generate revenue for the department. Furthermore, this led to improved hands-on training programs related to BSC use in laboratories working with biohazardous agents.